Health professionals’ experience of implementing and delivering a ‘Community Care’ programme in metropolitan Melbourne: a qualitative reflexive thematic analysis - Cylie Williams; Kelly-Ann Bowles; Brendan Shannon; Hollie Shannon; Nadine Andrew; Julia Morphet (BMJ Open)
Objectives To explore the experiences of health professionals involved in delivering a multidisciplinary Community Care programme that provides a transitional care coordination service for patients visiting a tertiary hospital service in Melbourne, Australia.Design Reflexive thematic analysis was used to identify themes from descriptions of delivering the programme, including its perceived strengths and challenges.Participants 12 healthcare professionals from four disciplines working in the Community Care programme were interviewed.Results Four themes were identified: (1) ‘increasingly complex’, depicts the experience of delivering care to patients with increasingly complex health needs; (2) ‘plugging unexpected gaps’, describes meeting patient’s healthcare needs; (3) ‘disconnected’, explains system-based issues which made participants feel disconnected from the wider health service; (4) ‘a misunderstood programme’, illustrates that a poor understanding of the programme within the health service is a barrier to patient enrolment which may have been exacerbated by a service name change.Conclusions The healthcare professionals involved in this study described the experience of providing care to patients as challenging, but felt they made a positive difference. By unravelling the patients’ health problems in context of their surroundings, they were able to recognise the increasingly complex patients’ health needs. The disconnection they faced to integrate within the wider healthcare system made their role at times difficult. This disconnection was partly contributed to by the fact that they felt the programme was misunderstood.